Algunos ejemplos del uso de internet en la clase de e/le - Fernandez Jódar, Raul (Wydawnictwo Naukowe UAM, 2003)
Internet is a new element which should be incorporated into the process of teaching foreign languages. The paper presents three practical examples of how to incorporate it into classes of Spanish as a foreign language.